Electron-Phonon Interactions in Low-Dimensional Structures - Challis, Lawrence (Oxford University Press, 2003)
The study of electrons and holes confined to two, one, and even zero dimensions has uncovered a rich variety of new physics and applications. This book describes the interaction between these confined carriers and the optic and acoustic phonons within and around the confined regions. Phonons provide the principal channel of energy transfer between the carriers and their surroundings and also the main restriction to their room temperature mobility. However, they also have many other roles; they contribute, for example, an essential feature to the operation of the quantum cascade laser. Since their momenta at relevant energies are well matched to those of electrons, they can also be used to probe electronic properties such as the confinement width of two-dimensional (2-D) electron gases and the dispersion curve of quasiparticles in the fractional quantum Hall effect. The book describes both the physics of the electron-phonon interaction in the different confined systems and the experimental and theoretical techniques that have been used in its investigation. The experimental methods include optical and transport techniques as well as techniques in which phonons are used as the experimental probe. This book provides an up-to-date review of the physics and its significance in device performance.